FORENSIC MEDICAL EXAMINATION: THE INFLUENCE OF EXTERNAL FACTORS - Saidov Akmal Abdulloevich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic medical examination plays a pivotal role in determining the cause and manner of death. However, the accuracy of these examinations can be significantly influenced by various external factors. This paper explores the impact of environmental conditions, scene preservation, time intervals, and observer biases on forensic findings. Understanding these influences is crucial for enhancing the reliability of forensic investigations.